Study of printability of new types of coated printing paper made from 100% recycled fibres - Jakucewicz, Stefan; Panák, Ján; Dreszer, Karol Henryk (Univerzita Pardubice, 2013)
The aim of this work was to evaluate the printability characteristics of the three types of coated paper made from recycled fibres in offset printing and to compare them with high-quality wood-free coated paper. Printing from test form was made on the sheet-fed offset B2 machine format. Inking was adjusted according to ISO 12647-2:2004. On the printed sheets were evaluated –ΔEab primary and secondary colours to the reference values, D100 CMYK inks, tonal value increase ΔAT, trapping and reproduction of fine elements. Based on these results we can say that the studied papers are in terms of printability exactly the same as high quality standard wood-free coated paper.
Keywords: recycled fibres; printing papers; offset printing; printability